2016
DOI: 10.1542/peds.2015-1829
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Utilization Among Children With the Highest Annual Inpatient Cost

Abstract: BACKGROUND AND OBJECTIVES: Children who experience high health care costs are increasingly enrolled in clinical initiatives to improve their health and contain costs. Hospitalization is a significant cost driver. We describe hospitalization trends for children with highest annual inpatient cost (CHIC) and identify characteristics associated with persistently high inpatient costs in subsequent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Our study expands upon the existing literature by employing a longitudinal, prospective design, and advanced analytic techniques. Consistent our findings, two publications using Medicaid data from the United States suggested that pediatric health care costs are mainly concentrated in a small group (5%‐10%) of children with distinctively high resource use, particularly those with a chronic respiratory condition . Another publication showed that a diagnosis of childhood asthma has been associated with being in the highest total cost quintile .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study expands upon the existing literature by employing a longitudinal, prospective design, and advanced analytic techniques. Consistent our findings, two publications using Medicaid data from the United States suggested that pediatric health care costs are mainly concentrated in a small group (5%‐10%) of children with distinctively high resource use, particularly those with a chronic respiratory condition . Another publication showed that a diagnosis of childhood asthma has been associated with being in the highest total cost quintile .…”
Section: Discussionsupporting
confidence: 89%
“…Children in the two HSU groups did not differ those with a chronic respiratory condition. 28 Another publication showed that a diagnosis of childhood asthma has been associated with being in the highest total cost quintile. 18 While these were retrospective studies focused on toddlerhood to adolescence, our study was based on a prospective birth cohort with healthy-born infants, which enabled the characterization of health care use from infancy on and efficient identification of prenatal and early-life risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…37 A small percentage of children make up the vast majority of health care spending in inpatient settings. 12 While it is clinically and politically relevant to understand the differences between medically complex and nonmedically complex health care spending, this study was unable to do so. Ongoing research is encouraged to understand how health care spending varies across these dimensions.…”
Section: Discussionmentioning
confidence: 88%
“…Regardless of the interpretation, the emerging literature seems consistent that persistently high spending is not guaranteed for most children. 16 Understanding the clinical attributes of children most likely to experience persistent high resource use might help inform clinical approaches to optimize their health. Similar to our findings, Zhong et al, 8 in a local-area study, also reported a strong correlation between a large number of chronic conditions and the likelihood of continued high resource use.…”
Section: Discussionmentioning
confidence: 99%
“…17 -23 Perhaps population health initiatives (eg, enhanced medical homes or neighborhoods for children with medical complexity, complex care networks) designed to alleviate these specific issues might benefit children who are the most likely to have persistent high resource use. 16 Most children with high inpatient costs are not hospitalized again in subsequent years. It remains unknown which reasons best explain this finding.…”
Section: Discussionmentioning
confidence: 99%